An in-depth analysis of Kuehne+ Nagel Ltd.'s challenges and prospects in the Bangladeshi freight forwarding market (Sea-Export) - Islam, Silma Subah (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.